PENGARUH APLIKASI TOPIKAL MADU, GEL Aloe vera, DAN MOIST EXPOSED BURN OINTMENT TERHADAP KEPADATAN KOLAGEN PADA PROSES PENYEMBUHAN LUKA BAKAR DERAJAT II TIKUS (Rattus norvegicus) - Ovelia Yolanda (2020)
Various scientific studies have proven that collagen is an ideal biomaterial in wound healing activities. Several bioactive compounds have been identified in honey, Aloe vera, and Moist Exposed Burn Ointment (MEBO) which contributed to increase collagen formation. The present study was conducted to compare the effect of topical application of honey, Aloe vera gel, and MEBO to collagen density in the healing process of second-degree burn wounds in rat. Twenty-eight male Wistar rats were randomly selected and divided into four groups: NaCl, honey, gel Aloe vera, and MEBO. The second-degree burns were made on the rat's posterior surface using an electric solder. Each group was treated topically, twice a day for six consecutive days. Skin biopsies were conducted on the seventh days, then stained using Hematoxylin eosin and the collagen density was calculated. One Way Anova test showed that the collagen density was significantly different between groups respectively (p=0,009). Post Hoc Multiple Comparison Bonferroni test showed that there were statistically significant differences between NaCl with honey (p=0,024) and NaCl with MEBO group (p=0,024). This present study indicate that topical application of honey and MEBO on the second-degree burns can increasing collagen formation, thus it can accelerate wound healing process.